IgE Generation and Mast Cell Activation. (January 2014) - Kritas, S.K.; Caraffa, A.; Antinolfi, P.; Saggini, A.; Pantalone, A.; Neri, G.; Rosati, M.; Tei, M.; Speziali, A.; Saggini, R.; Pandolfi, F.; Cerulli, G.; et al.
IgE is an important marker for allergy and plays a central role in the induction of allergic diseases through its binding of the high affinity receptor on mast cells. Mast cells can influence B cell survival, proliferation and differentiation into CD138 + cells. Among TH2 cytokines, interleukin (IL)-4 and IL-13 are responsible for class-switching in B cells which resolves in production of allergen-specific IgE antibodies that bind to specific receptor on mast cells. IgE synthesis by B cells is regulated by CD40 ligand, IL-4 and interferon-gamma, therefore inhibition of B cell antigen-specific IgE may prevent the cleavage of CD23 from B cells, having a therapeutic impact which also includes the removal of circulating free IgE, omalizumab, corticosteroids, mast cell stabilizers, leukotriene receptor antagonist, and others. B cell differentiation into IgE-producing cells requires two signals provided by TH2 cells and IL-4, however IL-4, IL-1 and IL-10 as well as several hormones are critical for the development of TH2 cells, while cytokines, such as interferon (IFN)-alpha, IFN-gamma, IL-12 and transforming growth factor (TGF)-beta play a negative role. However, the exact mechanism of this process has not yet been defined.